Potential Repositioning of Anti-cancer EGFR Inhibitors in Alzheimer's Disease: Current Perspectives and Challenging Prospects. (10th August 2021) - Mansour, Heba M.; Fawzy, Hala M.; El-Khatib, Aiman S.; Khattab, Mahmoud M.
Graphical abstract: Highlights: New therapeutic approaches have to be considered in Alzheimer's disease (AD). Pathways regulating cell duplication are significant targets. Tyrosine kinase inhibitors seem promising in treating AD. TKI repositioning in AD faces challenges, including safety and efficacy. Clinical trials using selective multiple-targeted BBB-permeable should be conducted. Abstract: Clinical trials of new drugs for Alzheimer's disease (AD) have ended with disappointing results, with tremendous resources and time. Repositioning of existing anti-cancer epidermal growth factor receptors (EGFR) inhibitors in various preclinical AD models has gained growing attention in recent years because hyperactivation of EGFR has been implicated in many neurodegenerative disorders, including AD. Many recent studies have established that EGFR inhibition suppresses reactive astrocytes, enhances autophagy, ameliorates Aβ toxicity, neuroinflammation, and regenerates axonal degradation. However, there is no incontrovertible neuroprotective proof using EGFR inhibitors due to many under-explored signaling transductions, poor blood–brain barrier (BBB) permeability of the most tested drugs, and disappointing outcomes of most clinical trials. This has caused debate about the possible involvement of EGFR inhibitors in future clinical trials. In this perspective article, we recap recent studies to merge data on the neuroprotective effects of EGFR inhibition. By consequent analysis of previous data, we notably find the under-investigated neuroprotective pathways that highlight the importance of additional research of EGFR inhibitors in attempts to be repurposed as burgeoning therapeutic strategies for AD. Finally, we will discuss future prospective challenges in the repositioning of EGFR inhibitors in AD.